Training Need of Farmers Related Crop Production in Madhya Pradesh (Indian Journal of Extension Education, 2009)
Training needs may be defined as the gap between job requirement and job performance or in other word, gap between "What is " and "What ought to be" in term of performance on the job. A proper assessment of training needs, especially in agriculture, while planning for the training of farmer and extension personal help in conducting effective training courses. Thus data was collected from 240 respondents by interview method with the help of wheel structure and pre tested schedule. They were asked about 14 area of training in relation to crop production technology. For measuring the respondent training need in the crop production rating scale was developed for which a simple numerical scoring method was used. Each item in the scale was provided with three alternative responses. It could be concluded from finding that the area of plant protection, weed management, and seed technology ranked 1, 2 & 3 and fertilizer application , organic farming, soil water conservation ranked 4, 5 & 6 was highly needed to the farmer. The relational analysis indicate that the land holding, material passion and awareness were positively and significant correlated with training needs, seed technology, land holding and income.